Pengaruh Faktor Pekerjaan Terhadap Tingkat Risiko Musculoskeletal Disorders (MSDs) Pada Tenaga Kerja di Sektor Pendidikan - Handoko, Lukman; Natsir Amrullah, Haidar; wahyuningtyas, wahyuningtyas (The Health Researcher's Journal, 2024)
Musculoskeletal disorders (MSDs) are a musculoskeletal disorder characterized by an injury to the muscles, tendons, ligaments, nerves, joints, cartilage, bones or blood vessels of the hands, feet, head, neck or back. MSDs can be caused or exacerbated by work, work environment and work performance. Musculoskeletal Disorders (MSDs) are one of the most common occupational diseases, ranking second among all cases of occupational diseases, in Indonesia the prevalence of musculoskeletal problems is 7.3%. The purpose of this study is to determine the contributing factors to the development of musculoskeletal disorders (MSDs) among employees in the education sector. A cross-sectional design was employed as the research methodology, and the sample size consisted of fifty education sector employees. Direct observation, in-person interviews using questionnaires, as well as taking pictures and videos of the work, were the methods used to collect data. Binary logistic regression was used for data analysis in order to ascertain the association between MSDs and work-related variables such as manual lifting, repetitive motions, and body position. The findings of the study indicated that 48% of participants complained of MSDs in the upper body, and most employees had bad posture. The results of the binary logistic regression test indicate a significant